The Evaluation of Aesthetic Values on the Two-Dimensional Visual Design Structure: Food Packaging Design - Raja Intan Suhaylah; Azman Bidin; Lim Yan Peng (Wacana Seni Journal of Arts Discourse, 2018)
The evaluation of aesthetics is often decoded as a subjective subject matter. Precisely, different respondents from diverse backgrounds may evaluate and own a different level of aesthetic evaluation. In addition, the presence of diverse design angles and perspectives are also inclined to produce contrasting evaluation from the viewers. As a pre-requisite, "What do I prefer the most?" and "What am I looking for?" are usually the essential questions posed by consumers with respect to the food packaging design. In particular, there are various design elements on a food packaging, which are devised according to the preferred visual cues. Then, these visual cues are perceived by the users of a particular product. Since previous studies revolved around packaging design and the end-users matter, this study aims to examine the impact of visual design elements toward people with design sensitivity. Also, there are numerous studies that have investigated the marketing values of small medium enterprise (SME) food products in Malaysia. However, this paper offers a concrete rationalisation by presenting evidence of a theoretical framework and highlights the relationship with people who have design sensitivity background. In general, the findings of this study can potentially contribute to the industry players in the form of managerial implications: packaging and graphic designers, product designers and the SME food producers. Comprehensively, this study discovered that individual differences may function as moderating variables that affect the product aesthetic evaluation with regards to the two-dimensional packaging design and its design elements. For instance, the implementation of mixed method approach, which involves two phases of studies has resulted in the qualitative findings in Phase 1. Based on the findings, it was ascertained that a few principles were affected by the subject of individual differences in appraising aesthetics. Specifically discussed in this paper is the result obtained from the first phase.